MEMBANGUN HELPING BEHAVIOR MELALUI SISTEM TANGGUNG RENTENG DI KOPERASI WANITA SETIA BHAKTI WANITA JAWA TIMUR - Suwangsih, Iwang (Media Mahardhika, 2020)
The purpose of this research is to know how helping behavior is made in Women Cooperative, Setia Bhakti Wanita Jawa Timur. This research is qualitative research with descriptive design. The data can be collected by interview many resources as one of founder this cooperative, leaders and assistant leaders, group coordinators, members and employees of this cooperative. The finding of this research is that helping behavior can be made because this cooperative uses joint responsibility system not only as a system to manage the cooperative business but it is used as organizational culture of this cooperative. So each people in this cooperative must do this organizational culture in daily life.